Exploring The Link Between Gratitude and Negative Emotions in Female Islamic Boarding Students - Al Karim, Chamilul Hikam; Suparno, Suparno; Hyoscyamina, Darorsy Endah; Listiara, Anita; Widodo, Prasetyo Budi (Developmental and Clinical Psychology, 2025)
This study explores the relationship between gratitude and negative emotions among female students in an Islamic boarding school (pesantren) in Tegal Regency, Indonesia. A total of 219 students aged 12–21 years participated in this study. Data were collected using validated scales to assess gratitude as well as symptoms of stress, anxiety, and depression. The results showed that gratitude was negatively correlated with stress (r = –0.236), anxiety (r = – 0.202), and depression (r = –0.339), indicating that higher levels of gratitude tend to be associated with lower levels of these negative emotional states. Descriptively, over half of the participants (57.53%) reported high levels of gratitude. Most students experienced normal levels of stress and depression, but a notable proportion (31.51%) experienced extremely severe anxiety. These findings underscore the relevance of gratitude in supporting emotional well-being, while also pointing to the urgent need for interventions targeting anxiety among students.